2015
DOI: 10.1097/coc.0b013e3182a790ce
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Abiraterone Acetate in Castration-resistant Prostate Cancer Patients With Concomitant Cardiovascular Risk Factors

Abstract: AA appears to be safe and well tolerated even in patients with cardiovascular comorbidities or with increased risk factors for cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…A recent observational study conducted in Italy showed the cardiac safety of abiraterone acetate [22]. Our different findings may be explained by subtle differences in the patient population in terms of higher cardiovascular risk and prior use of ketoconazole, which was used in two out of five patients who had a cardiac SAE.…”
Section: Discussionmentioning
confidence: 57%
“…A recent observational study conducted in Italy showed the cardiac safety of abiraterone acetate [22]. Our different findings may be explained by subtle differences in the patient population in terms of higher cardiovascular risk and prior use of ketoconazole, which was used in two out of five patients who had a cardiac SAE.…”
Section: Discussionmentioning
confidence: 57%
“…For patients with CRPC and concurrent cardiovascular comorbidities, these side-effects can pose added risks. The cardiovascular outcomes of abiraterone treatment in 51 patients with mCRPC with cardiovascular comorbidities treated with standard doses of abiraterone and prednisone were assessed 58. Comorbidities included controlled hypertension (41%), cardiac ischemia (14%), stroke (9%), dyslipidemia (18%) and hyperglycemia (30%).…”
Section: Effects Of Abiraterone On Quality Of Life and Specific Patiementioning
confidence: 99%
“…Full details of the study methods have been published previously [Procopio et al 2015]. Briefly, patients were ⩾18 years old, had received ⩾1 docetaxel-based regimen, their Eastern Cooperative Oncology group (ECOG) performance status (PS) was ⩽2 and their life expectancy was ⩾3 months.…”
Section: Methodsmentioning
confidence: 99%